Role of Mechanization in Crop Residue Management in Telangana - Jagadeeshwar, R.; Jagadeeshwar, R.; Ramanjaneyulu, A. V.; Rajaiah, P.; Kumar, M. Vijaya; Sudhakar, C.; Manjulatha, G.; Chauhan, Sreedhar (Chronicle of Bioresource Management, 2023)
Huge quantity of crop residues are generated every season in India. Further, considerable amount of it is being burnt by farmers to make way for planting subsequent crops. But, it is causing environmental pollution and emitting green house gases besides loss of soil health and quality. Among many ways, mechanization was found effective in managing the residues. With the advent of various machinery for harvesting and threshing, cutting and incorporation of left over stubbles in the soil, residue management has gained momentum. Further, surplus residues can be utilized for cattle feed, soil health improvement, compost making, power generation, biofuel production and in various industries. Mechanized crop residue management plays a greater role in improving soil health in case of organic farming based crop production. In this article, we have given an overview of role of mechanization in crop residue management.